Motions of Curves in the Projective Plane Inducing the Kaup-Kupershmidt Hierarchy - Musso, E. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
The equation of a motion of curves in the projective plane is deduced. Local flows are defined in terms of polynomial differential functions. A family of local flows inducing the Kaup-Kupershmidt hierarchy is constructed. The integration of the congruence curves is discussed. Local motions defined by the traveling wave cnoidal solutions of the fifth-order Kaup-Kupershmidt equation are described.